Modeliranje pokrajine - Ciglič, Rok; Geršič, Matjaž; Perko, Drago; Zorn, Matija (GIS v Sloveniji, 2020)
Modeliranje pokrajine ('Modelling landscape') is the fifteenth volume in the series GIS v Sloveniji (GIS in Slovenia). The goal of the volume is to present the wide variety of research findings on geographical information systems in Slovenia in recent years. Powerful geoinformatic tools and precise data facilitate research on processes and phenomena, and their modelling. The volume presents project outputs and research results in areas such as geology, geomorphology, hydrology, environmental protection, geography, surveying, archaeology, transport, telecommunication infrastructure, tourism, cultural heritage, remote sensing, and others. Readers will discover new features regarding the applicability of geographical information systems and will learn about interesting research findings in many areas.